2007
DOI: 10.1149/1.2798674
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Alloying of Copper Substrate with Tin Using Ionic Liquid as an Electrolyte at Medium-Low Temperatures

Abstract: Electrochemical alloying of Cu substrate through a reduction-diffusion method was investigated using ionic liquid, trimethyl-n-hexylammonium bis[(trifluoromethyl)sulfonyl]amide, as a solvent for an electrolytic bath. The use of the ionic liquid rendered it possible to raise the processing temperature beyond 100 åC so as to form the Cu-Sn layers faster than in the case of an aqueous media. The layers obtained from Cu thin layer under potentiostatic condition were silver-gray speculum metal composed of Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…33 The formation and growth of deposited metal−substrate metal alloys are also expected in systems forming intermetallic phases between the substrate and depositing metals, 54 as observed for several combinations. 54−57 According to the existing models, the formation and growth of the ICL occur via the following steps: 58,59 (1) Tin atoms are deposited at the copper surface. (2) The growth of the ICL is initiated by a site exchange between copper atoms and vacancy 4) The successive deposition of tin occurs at the surface of the ICL.…”
Section: ■ Discussionmentioning
confidence: 99%
“…33 The formation and growth of deposited metal−substrate metal alloys are also expected in systems forming intermetallic phases between the substrate and depositing metals, 54 as observed for several combinations. 54−57 According to the existing models, the formation and growth of the ICL occur via the following steps: 58,59 (1) Tin atoms are deposited at the copper surface. (2) The growth of the ICL is initiated by a site exchange between copper atoms and vacancy 4) The successive deposition of tin occurs at the surface of the ICL.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Although the technology is generally considered to be a soft-solution process, the treatment of waste deposition baths, which have a high entropy since they contain two or more metal components, is energy-consuming in some cases. In contrast, we recently demonstrated that "speculum" Cu-Sn alloy layers can be formed on a Cu substrate by a reduction-diffusion (RD) method using electrochemical contact immersion (i.e., galvanic contact) [1] or potentiostatic process [2]. For the continuous growth of Cu-Sn alloy by the RD process, rapid diffusion of deposited Sn atoms into the Cu substrate to form the alloy phase is essential.Here, we employed an ionic liquid (IL), trimethyl-nhexylammonium bis[(trifluoromethyl)sulfonyl]amide (TMHA-Tf 2 N), as a non-volatile and non-flammable solvent for the process, and it was found that the use of TMHA-Tf 2 N made it possible to raise the processing temperature up to 150 ˚C [1].…”
mentioning
confidence: 99%